A comparative study on takaful regulations in Malaysia and Indonesia - Noor Mizan Arifin
The Takaful industry had to undergo globalization, which changes many aspects, including Takaful rules and regulations. One of the main challenges faced by the Takaful industry is the lack of a simplified regulatory framework across borders that can support the development for larger regional players. Thus, the objectives of this study are to identify the impacts of globalisation on Takaful rules and regulations, to compare the current Takaful rules and regulations in Malaysia and Indonesia and lastly to suggest for a comparative analysis on Takaful rules and regulations for the benefit of Takaful operators in Malaysia and Indonesia. This qualitative study focused on multiple case studies. The population was made up of Takaful operators and the respondents were chief executive officers and the top management from six Takaful operators in Malaysia and Indonesia. Data was collected from face-to-face and semistructured interviews. These raw data, which were verbatim transcripts, were organized and compiled for data analysis. The data were analyzed using the Atlas.ti version 7 software program. Analysis involved the process of creating a theme, interrelating the theme, coding and finally, preparing for a report finding. This study identified the process of globalisation; it primarily focused on the deregulation, liberalisation, and detariffication, which influenced the rules and regulations of Takaful in Malaysia and Indonesia. From the study, most of the Takaful operators in Malaysia believed that there are many aspects of globalisation that affect the detarrifed Takaful rule and regulation . Meanwhile, the Takaful Indonesian operators found that Open Market is the main aspect of globalisation that affects Takaful rules and regulations. After recognising the act used in both countries, this study also identified the similarities and differences between both acts. This study confirms that the Islamic Financial Services Act 2013 (IFSA 2013) and Undang-Undang No. 40 (UU40) tog ther with Peraturan Otaritas Jasa Kewangan No. 23 (POJK 23) are the main acts used in Malaysia and Indonesia. There are thirteen similarities and eight differences between these three acts. Finally, this study has successfully provided a comparative analysis on Takaful rules and regulations that are used by Takaful operators in Malaysia and Indonesia. The comparative analysis of Takaful rules and regulations provides a significant contribution to Takaful operators during the era of globalisation in both countries. This study also adds on to the extension of literature where future researchers may use this study as a starting point to explore other aspects regarding Takaful regulations. To conclude, this comparative analysis can be useful as a self-accessed supporting tool and time-effective reference for the Takaful operators in Malaysia and Indonesia.